High N2 Fixation in and Near the Gulf Stream Consistent with a Circulation Control on Diazotrophy. Issue 16 (11th August 2020) - Palter, Jaime B.; Ames, Elana J.; Benavides, Mar; Gonçalves Neto, Afonso; Granger, Julie; Moisander, Pia H.; Watkins‐Brandt, Katie S.; White, Angelicque E.
Abstract: The stoichiometry of physical nutrient supply may provide a constraint on the spatial distribution and rate of marine nitrogen (N2 ) fixation. Yet agreement between the N2 fixation rates inferred from nutrient supply and those directly measured has been lacking. The relative transport of phosphate and nitrate across the Gulf Stream suggests that 3–6 Tg N year −1 must be fixed to maintain steady nutrient stoichiometry in the North Atlantic subtropical gyre. Here we show direct measurements of N2 fixation consistent with these estimates, suggesting elevated N2 fixation in and near the Gulf Stream. At some locations across the Gulf Stream, we measured diazotroph abundances and N2 fixation rates that are 1–3 orders of magnitude greater than previously measured in the central North Atlantic subtropical gyre. In combination, rate measurements and gene abundances suggest that biogeochemical budgets can be a robust predictive tool for N2 fixation hot spots in the global ocean. Plain Language Summary: Marine photosynthetic organisms face a unique challenge: They are confined to the ocean's near‐surface layer where there is sufficient light for photosynthesis, yet the nutrients needed for growth are rapidly stripped from these layers. In response to this nutrient scarcity, some microorganisms, called diazotrophs, evolved the ability to tap into alternative resources: They convert the nitrogen gas that comprises a majority of the atmosphere and is abundantly dissolved in seawater into ammonium needed for growth. Diazotrophs regulate the rate of new nitrogen input to the ocean, which influences the productivity of marine fisheries, as well as how carbon dioxide is partitioned between the atmosphere (where it contributes to the greenhouse effect) and the ocean (where it does not). Therefore, understanding the controls on diazotrophy is a key oceanographic objective. It was previously hypothesized that the Gulf Stream region could be a hot spot of nitrogen fixation. In this work, we tested this hypothesis by measuring nitrogen fixation rates and diazotroph abundances across the Gulf Stream. We found robust diazotrophy, far exceeding that previously measured in the subtropical North Atlantic. Understanding the linkages between ocean circulation and N2 fixation helps us assess the vulnerability or stability of ocean biology and chemistry to future change. Key Points: The stoichiometry of nutrient supply predicts high N2 fixation rates in/near Gulf Stream Measured N2 fixation rates in surface waters match expectations from a P* budget (order 10 nmol N L −1  day −1 ) Molecular analyses and microscopy confirm robust diazotrophy, with gradients possibly caused by convergent flow